Lithic assemblages in the Middle Stone Age: Products, productions, organizations and evolution - (:unkn) unknown (My University, 2023)
At the end of the Middle Pleistocene, in North Africa, cultural complexes have co-existed. The identification and definition of these techno-complexes have been debated for more than a century. One of the important issues of Paleolithic research in North Africa is the understanding of the relationship between the North African Middle Stone Age and Aterian industries. For this reason, precise definitions of these complexes are essential.Typo-technological approaches to lithic equip...
Keywords: African Research